Solarizing the moon : essays in honour of Lionel Sims - Sims, Lionel,; Silva Vallejo, Fabio, 1962-; Henty, Liz, (Archaeopress Archaeology, 2022)
Lionel Sims has produced an influential body of work that has challenged existing narratives about British prehistoric monuments and provided innovative ways to approach and think about skyscapes. This book, in his honour, is divided into three parts: anthropology and human origins, prehistory and megalithic monuments, and theory.